1990
DOI: 10.1159/000205022
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Thrombocytopenia: Definition, Incidence and Natural History

Abstract: We have sought to clarify the definition and importance of newly diagnosed thrombocytopenia in pregnant women by establishing an appropriate reference interval for the platelet count, and by observing the outcome in a cohort of thrombocytopenic pregnant women. The mean platelet count was lower in 2,155 healthy pregnant than non-pregnant women, and varied with race, but did not fall with increasing gestation, except in Black women. 101 of approximately 2,800 women became newly thrombocytopenic during pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
3
4

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 14 publications
5
38
3
4
Order By: Relevance
“…Thus, the prevalence of thrombocytopenia in Indian population is similar to world literature (5-12%). The present study found no influence of age and religion on prevalence of thrombocytopenia in pregnancy similar to Mathews et al [6]. 96.3% of controls and 95.7% of cases were enrolled in third trimester since most antenatal women in our population seek advice in late pregnancy or when a complication arises.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the prevalence of thrombocytopenia in Indian population is similar to world literature (5-12%). The present study found no influence of age and religion on prevalence of thrombocytopenia in pregnancy similar to Mathews et al [6]. 96.3% of controls and 95.7% of cases were enrolled in third trimester since most antenatal women in our population seek advice in late pregnancy or when a complication arises.…”
Section: Discussionsupporting
confidence: 88%
“…This figure was higher than figures of 11.6% reported by Boehlen et al in and 7.2% reported by Sainio et al 2,3 The higher prevalence in this study may be because of malaria and dengue infections. The present study found no influence of age and religion on prevalence of thrombocytopenia in pregnancy like Mathews et al 10 From our findings, gestational thrombocytopenia occurred across the three trimesters. No case of severe thrombocytopenia was seen in first trimester.…”
Section: Discussioncontrasting
confidence: 57%
“…Increased blood volume, increased platelet activation, and increased platelet clearance contribute to a 'physiologic' decrease in platelet count during pregnancy [4]. Gestational thrombocytopenia is considered to be the most prevalent cause of thrombocytopenia in pregnancy and accounts for about 75% of cases its cases during pregnancy.…”
Section: Introductionmentioning
confidence: 99%